Bad hare day - Moss, Miriam; Chapman, Lynne, 1960- (New York : Bloomsbury Children$1 (Bs Books :s Distributed to the trade by Holtzbrink Pub., 2003)
Uncle Herbert the Hare, the best hairdresser in town, has his hands full when his niece Holly spends time at his salon.
Keywords: Hairdressing -- Fiction; Behavior -- Fiction; Uncles -- Fiction; Hares -- Fiction; Animals -- Fiction